Flatness-based Trajectory-tracking Control of Dielectric Elastomer Actuators. Issue 2 (2020) - Scherer, P.M.; Irscheid, A.; Rizzello, G.; Rudolph, J.
Abstract: In recent years, actuators based on dielectric elastomers have become popular for both research and industrial applications. Due to their nonlinear behavior, they are typically used in on/off actuation. Established feedback control methods such as PID provide an effective and robust way to drive these actuators under constant setpoint requirements. However, such control methods exhibit poor trajectory tracking performance. This shortcoming is addressed in this work with a flatness-based nonlinear control design for a circular membrane actuator based on dielectric elastomers. By exploiting a nonlinear electro-mechanical model of the device, a tracking control law is designed in both feed-forward and feedback form. Moreover, it is shown how the flatness-based feed-forward control may be used to extend a conventional PID control to improve its tracking performance. The presented methods are validated and compared experimentally with a real actuator prototype. Tracking accuracy better than 10µm along a 1 mm stroke trajectory (i. e. less than 1%) is shown. This result is a significant improvement over existing PID control laws.